2008
DOI: 10.1016/j.drugalcdep.2007.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Mortality prior to, during and after opioid maintenance treatment (OMT): A national prospective cross-registry study

Abstract: OMT significantly reduces risk of mortality also when examined in an intention-to-treat perspective. Studies that evaluate effects of OMT only in patients retained in treatment tend to overestimate benefits. Levels of overdose mortality will influence the risk reduction. Cross-registry studies as the current one are an important supplement to other observational designs in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
159
2
11

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(182 citation statements)
references
References 86 publications
8
159
2
11
Order By: Relevance
“…Staying abreast of emerging data will provide better understanding on how to manage patients with substance use disorder. Our knowledge of the genetics underlying predisposition to addiction [6][7][8], alterations in neurotransmitter tone [38,39], and how reward deficiency is contributing to stress and relapse [40] will supply us with a more sophisticated and heuristically useful view of the patient's physiological condition and allow for a more individualized approach.…”
Section: Resultsmentioning
confidence: 99%
“…Staying abreast of emerging data will provide better understanding on how to manage patients with substance use disorder. Our knowledge of the genetics underlying predisposition to addiction [6][7][8], alterations in neurotransmitter tone [38,39], and how reward deficiency is contributing to stress and relapse [40] will supply us with a more sophisticated and heuristically useful view of the patient's physiological condition and allow for a more individualized approach.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that there is a high mortality rate among drug users, and that death by overdose is common cause of death in that group (Clausen et al, 2008;Darke and Degenhardt, 2007;Davoli et al, 2007;Bargagli et al, 2006;Johnson et al, 2005;Gossop et al, 2002). Actually, deaths from opiate overdose comprise the vast majority of all drugrelated deaths (Strang et al, 2008;Darke and Zador, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that patients who leave methadone programmes have increased mortality risks relative to those remaining in treatment. ( Caplehorn, Dalton, Haldar, Petrenas, & et al, 1996;Clausen, Anchersen, & Waal, 2008;Davoli, et al, 2007;Fugelstad, Stenbacka, Leifman, Nylander, & Thiblin, 2007;Langendam, van Brussel, Coutinho, & van Ameijden, 2001;Zanis & Woody, 1998) A recent prospective cohort study of Italian opiate users found that the risk of overdose following treatment cessation was more than three times higher in the first 30 days after treatment drop-out or discharge compared to the subsequent 31 days or more after treatment. (Davoli, et al, 2007) However, these effects are not specific to MMT but rather a range of treatments for heroin dependence, including MMT, methadone detoxification, other pharmacological detoxification and psychological interventions.…”
Section: Introductionmentioning
confidence: 99%